Color struck: essay on race and ethnicity in global perspective - Adekunle,Julis O.(ed.); Williams, Hettie V. (ed.) (Lanham University press of America, 2010)
Color Struck: Essays of Race and Ethnicity in Global Perspective is a compilation of expositions on race and ethnicity, written from multiple disciplinary approaches including history, sociology, women's studies, and anthropology. This book is organized around a topical, chronological framework and is divided into three sections, beginning with the earliest times to the contemporary world. The term "race" has nearly become synonymous with the word "ethnicity," given the most recent findings in the study of human genetics that have led to the mapping of human DNA. Color Struck attempts to answer questions and provide scholarly insight into issues related to race and ethnicity.
Keywords: Mixed race-United States